A 20‐year long term experience of the Italian Diamond‐Blackfan Anaemia Registry: RPS and RPL genes, different faces of the same disease?. (21st February 2020) - Quarello, Paola; Garelli, Emanuela; Carando, Adriana; Cillario, Rebecca; Brusco, Alfredo; Giorgio, Elisa; Ferrante, Daniela; Corti, Paola; Zecca, Marco; Luciani, Matteo; Pierri, Filomena; Putti, Maria C.; et al.
Summary: Diamond–Blackfan anaemia (DBA) is a rare and heterogeneous disease characterised by hypoplastic anaemia, congenital anomalies and a predisposition for malignancies. The aim of this paper is to report the findings from the Italian DBA Registry, and to discuss the Registry's future challenges in tackling this disease. Our 20‐year long work allowed the connection of 50 Italian Association of Paediatric Haematology and Oncology (AIEOP) centres and the recruitment of 283 cases. Almost all patients have been characterised at a molecular level (96%, 271/283), finding a causative mutation in 68% (184/271). We confirm the importance of determination of erythrocyte adenosine deaminase activity (eADA) and of ribosomal RNA assay in the diagnostic pipeline and characterisation of a remission state. Patients with mutations in large ribosomal subunit protein ( RPL ) genes had a significant correlation with the incidence of malformations, higher eADA levels and more severe outcomes, compared to patients with mutations in small ribosomal subunit protein ( RPS ) genes. Furthermore, as a consequence of our findings, particularly the incidence of malignancies and the high percentage of patients aged >18 years, we stress the importance of collaboration with adult clinicians to guarantee regular multi‐specialist follow‐up. In conclusion, this study highlights the importance of national registries to increase our understanding and improve management of this complex disease.